The efficacy of neoadjuvant chemotherapy in invasive bladder cancer - (:unkn) unknown (Akademiai Kiado Rt., 2002)
Radical cystectomy is the gold standard in the treatment of invasive bladder cancer. However, five-year disease-free survival is low most probably due to micrometastatic disease at the time of surgery. The neoadjuvant chemotherapy may be performed as the first line management for invasive bladder tumors in order to treat micrometastases found at the diagnosis and improve resectability of larger neoplasms. A total of 43 patients diagnosed with invasive bladder tumors and 11 patients received neoadjuvant chemotherapy. The mean age of patients was 64 (43-74) years, and mean follow-up period was 52 months (12-114). Neoadjuvant chemotherapy protocol consisted of methotrexate, vinblastine, doxorubicin, and cisplatin (MVAC) or cisplatin, methotrexate, and cisplatin (CMV). All patients in neoadjuvant chemotherapy group underwent radical cystectomy. There was no significant difference between the groups with respect to disease-free survival time and overall survival time. In patients who received neoadjuvant chemotherapy, the respective disease-free and overall survival times were 31 months and 36 months versus 30 months and 35 months in patients who were treated with surgery only (p > 0.05). Five-year survival rates were 36% and 31% in the chemotherapy and no-chemotherapy groups, respectively. In the present study, 5-year survival rate was not affected by neoadjuvant chemotherapy in invasive bladder tumor. Complete pathological remission (stage p0) was found in 28% and pathological downstaging (stage < T2) was seen in 9% of patients in the neoadjuvant chemotherapy group. Five-year survival rates were 75% and 14.2% in patients who responded to chemotherapy, and in patients with no response, respectively (p < 0.05). The most favorable prognostic factor in this study was the response to neoadjuvant chemotherapy revealed as complete remission or pathological downstaging. The most important issue remains the prediction of patients who would respond and benefit from neoadjuvant chemotherapy.
Keywords: Invasive bladder cancer; Neoadjuvant chemotherapy; Survival